Climate change, media & culture : critical issues in global environmental communication - Pinto, Juliet; Gutsche, Robert E., Jr., 1980-; Prado, Paola (Emerald Publishing Limited, 2019)
The acceleration of global climate change creates a nexus for the examination of power, political rhetoric, science communication, and sustainable development. This book takes an international view of twenty first century environmental communication to critically explore mediated expressions of climate change.